Codhi' Sumekar dance Estetika Tari Codhi' Sumekar Karya Taufikurrahman Di Kabupaten Sumenep: Estetika Tari Codhi' Sumekar Karya Taufikurrahman Di Kabupaten Sumenep - Halima, Nur; Rahayu, Eko Wahyuni (APRON Jurnal Pemikiran Seni Pertunjukan, 2021)
Codhi' Sumekar dance is a choreographic work of Taufikurrahman, a founder of the Bhumi Jokotole Dance Studio in Sumenep City. Codhi' Sumekar dance is in the form of a paired female dance, which describes the skills and toughness of Madurese women in practicing codhi' weapons to maintain their safety, dignity and honor. This dance form is equipped with a property in the form of codhi' (dagger or small dagger) which is a weapon commonly used by women in the past. The author's interest in choosing the topic of aesthetic studies is because he sees the uniqueness of this Codhi 'Sumekar Dance which lies in the dynamic, firm movement patterns, the properties used have multiple functions, and still exist not only in society but also among students. In addition, the form and style of the Codhi 'Sumekar Dance show very distinctive Madurese characteristics both in terms of movement patterns and dance music. This study aims to reveal the form and aesthetic value of the form of Codhi' Sumekar Dance, using the form theory approach as revealed by Soedarsono (1978), the aesthetic theory expressed by Elizabeth R. Hayes (1959), supported also by literature on Madurese culture. The research was conducted using qualitative methods, with data collection techniques through: literature study, observation, interviews and documentation and documentation. Data analysis was carried out using data reduction techniques, data classification, data presentation and drawing conclusions. The results showed that the form of Codhi 'Sumekar Dance structurally consists of 5 parts including: opening part, main part 1, main 2, main 3 and closing. All of these sections are supported by 26 types of motion motifs. In addition, the unified form of the Codhi' Sumekar Dance is visually supported by a distinctive fashion makeup design using karompi monte and calana tello' per empa'. Dance music using gamelan. The property uses a small kris (codhi'). Elements of the aesthetic value of Codhi' Sumekar Dance can be seen using the aesthetic concept of Elizabeth R. Hayes, namely unity, variety, repetition, contrast, transition, sequence, climax, proportion, balance, and harmony. In addition to these ten elements, the aesthetic or beauty of the Codhi' Sumekar Dance is also in accordance with the Madurese background and style which is then supported by movement motifs with Madurese techniques and dance music using Madurese language song.